Editorial. Monográfico: Género y sexualidad: nuevos enfoques terapéuticos - del Río Olvera, F. Javier; García Rojas, Antonio Daniel (Revista de Psicoterapia, 2024)
Editorial. Monográfico: Género y sexualidad: nuevos enfoques terapéuticos